Applying Feature-Oriented Software Development in SaaS Systems: Real Experience, Measurements, and Findings - Oscar Pedreira; Fernando Silva-Coira; Ángeles Saavedra Places; Miguel R. Luaces; Leticia González Folgueira (Journal of Web Engineering, 2019)
Distributing software as a service (SaaS) has become a major trend for web-based systems. However, this software distribution model poses many challenges. One of them is feature variability, that is, some features of the system may be required by some users, but not by all of them. In addition, variability is more complex than just including or excluding a feature, since different types of relationships may exist between features. The implementation of this variability, and the parametrization and configuration of the system can be complex in this context, so the development process of a SaaS system must adequately address variability management. In this paper we present an experience applying feature oriented software development (FOSD) in the context of SaaS web-based systems development. We present a real experience in the development of a web-based system for managing home care services for dependent people. The article describes the problem of variability management in this domain, and the feature model of the system. Finally, we present an empirical evaluation of the feature model of the system based on data obtained from its real deployment after two years of use. The empirical evaluation was based on state-of-the-art measures for variability management, and revealed relevant insights for software development in this context.